Productivity parameters and protein quality characteristics of wheat cultivars in response to nitrogen fertilization - Bressiani, Joseane; Oro, Tatiana; Santetti, Gabriela; Valério, Igor; Gutkoski, Luiz Carlos (Revista de Ciências Agroveterinárias, 2018)
Nitrogen fertilization strategies using increasing dosages demonstrate favorable effects on grain yield and quality; however, differences in results have been reported in relation to the effect of dosages, times and application schedules throughout the development cycle of the crop. The objective of this study was to evaluate the productivity and protein quality characteristics in response to nitrogen fertilization management applied to the cultivars TBIO Itaipu, TBIO Pioneiro, TBIO Quartzo and TBIO Seleto. The experimental design in randomized blocks with three replications, in a factorial scheme (4 cultivars x 7) handlings was used. The experiment was conducted in Coxilha, RS, during the agricultural years of 2012 and 2013. The total dose of N used in the present work was 140 kg ha-1, with 30 kg ha-1 of N being applied at sowing and remainder in coverage, for the time defined in each treatment. The grain yield of the studied cultivars was increased with the nitrogen fertilization applied in a concentrated way in the treatment T2 and showed a negative correlation with the protein content, showing that the genotypic superiority to the yield of grains can negatively affect the protein ratio. Of the cultivars studied TBIO Pioneiro stood out from the others regarding the general gluten strength in the 2012 crop and the TBIO Seleto was superior in the 2013 crop, however, the protein content did not show a significant association with the gluten strength, revealing that the concentration was not efficient to predict industrial quality.